Wireless control quadcopter with stereo camera and self-balancing system - Vechian, Mongkhun Qetkeaw (2012)
This research focused on develops a remotely operated Quadcopter system. The Quadcopter is controlled through graphical user interface (GUI). Communication between GUI and Quadcopter is done by using wireless communication system. The Quadcopter balancing condition is sensed by FY90 controller and IMU 5DOF sensor. For smooth landing, Quadcopter is equipped with ultrasonic sensor. All signals from sensors are processed by Arduino Uno microcontroller board. Output from Arduino Uno microcontroller board used to control Quadcopter propellers. GUI is designed using Visual Basic 2008 Express as interface between control base and Quadcopter. The experiment shows that Quadcopter can hover with maintain it balancing and stability. Quadcopter can accept load disturbance up to 250g during it hover condition. Maximum operated time of Quadcopter is six minutes using 2200mAh Lipo battery and operate time can be increase by using largest battery capacity.